2016
DOI: 10.1097/md.0000000000004743
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of relative oxycodone consumption in surgical pleth index-guided analgesia versus conventional analgesia during sevoflurane anesthesia

Abstract: Background:The surgical pleth index (SPI) is proposed for titration of analgesic drugs during general anesthesia. Several reports have investigated the effect of SPI on the consumption of opioids including remifentanil, fentanyl, and sufentanil during anesthesia, but there are no reports about oxycodone. We aimed to investigate intravenous oxycodone consumption between SPI-guided analgesia and conventional analgesia practices during sevoflurane anesthesia in patients undergoing thyroidectomy.Methods:Forty-five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 19 publications
1
60
1
1
Order By: Relevance
“…A total of 1045 patients were studied, with 520 receiving an intervention compared to 526 treated according to routine clinical care. Care guided using the SPI was evaluated in six studies [16][17][18][19][20][21] followed by the ANI in three studies [22][23][24]. The NOL, pupillometry and the beat-to-beat cardiovascular depth of anesthesia index (CARDEAN 2.0) were evaluated in single studies [15,25,26].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1045 patients were studied, with 520 receiving an intervention compared to 526 treated according to routine clinical care. Care guided using the SPI was evaluated in six studies [16][17][18][19][20][21] followed by the ANI in three studies [22][23][24]. The NOL, pupillometry and the beat-to-beat cardiovascular depth of anesthesia index (CARDEAN 2.0) were evaluated in single studies [15,25,26].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Six reports were identified that compared SPI guided anesthesia to standard practice [16][17][18][19][20][21]. Studies were diverse with regard to the maintenance hypnotic (propofol or sevoflurane) and opioids (remifentanil/sufentanil/ fentanyl and oxycodone).…”
Section: Surgical Plethysmographic Index (Spi)mentioning
confidence: 99%
“…Therefore, several monitoring tools including ANI, Surgical Pleth Index (SPI), and Nociception level (NoL) have been developed to evaluate nociception during general anesthesia through the analysis of the relative parasympathetic tone. Researches have shown that these tools might reflect the nociception during general anesthesia [1,16,21]. However, these parameters are mainly aimed at adult patients and affected by arrhythmia alongside many heart rate affecting drugs [6,25].…”
Section: Discussionmentioning
confidence: 99%
“…For pediatric patients younger than 4 years old, 0.5mg/kg midazolam PO 20-30 mins before entering the operating room, other patients did not receive any premedication. On arrival in the operation room, intravenous access and basic monitoring with an electrocardiogram, and pulse oximetry were established, and a crystalloid infusion was started following 4-2-1 principals [16]. Noninvasive blood pressure in the arm was recorded every 1 min during the experiment.…”
Section: Anesthetic Techniquementioning
confidence: 99%
See 1 more Smart Citation